AB1358-HPR DIAGNOSIS OF AXIAL SPONDYLOARTHRITIS: A PRIMARY UNMET EDUCATIONAL NEED FOR RHEUMATOLOGISTS. (13th June 2020) - Maksymowych, W. P.; Caplan, L.; Deodhar, A.; Dolatabadi, S.; Hwang, M.; Carlson, A.; Steed, K.; Carapellucci, A.; Paschke, J.; Gensler, L. S.
Abstract : Background: Diagnosis of axial spondyloarthritis (axSpA) is challenging because of absent physical findings in early disease and the limited diagnostic performance of laboratory markers. Considerable reliance is placed on imaging of the sacroiliac joints (SIJ) but specialty training is primarily focused on interpretation of plain radiographic abnormalities. Objectives: We aimed to identify what might be the primary unmet educational needs of rheumatologists completing fellowship training by using clinical and imaging data from an inception cohort of patients presenting with undiagnosed back pain. We hypothesized that concordance would increase after imaging is reviewed after the clinical data. Methods: The diagnosis of axSpA was compared between local rheumatologists, axSpA experts and pF using clinical and imaging data from the multicenter Screening for Axial Spondyloarthritis in Psoriasis, Iritis, and Colitis (SASPIC) Study. In this inception cohort, patients ≤45 years of age with ≥3 months back pain undergo diagnostic evaluation by a local SASPIC rheumatologist, including imaging of the SIJ, who then records a global evaluation of presence/absence of axial SpA. This is done at 3 consecutive stages: 1.After the clinical evaluation. 2.After the results of labs (HLA B27, CRP) and radiography. 3.After review of the local MRI. In this exercise, 20 cases were selected from the SASPIC cohort and the rheumatologist global evaluations were removed from the eCRFs. Four experts in axSpA reviewed the clinical and imaging data in each eCRF and provided their global evaluations for stages 1, 2, and 3 of these 20 cases. Subsequently, 4 pF rheumatologists conducted the same exercise blinded to the assessments of the local rheumatologist and experts in axSpA. Concordance (% agreement) between the assessors was analyzed. Results: Diagnosis of axSpA by the local SASPIC rheumatologist was made in 90%, 65%, and 75% of cases after stages 1, 2, and 3, respectively. Majority diagnosis of axSpA by experts was made in 84.2% (16/19), 57.9% (11/19), and 63.2% (12/19), after stages 1, 2, and 3, respectively. Majority diagnosis of axSpA by pF rheumatologists was made in 94.4% (17/18), 100% (16/16), and 93.8% (15/16). Concordance among experts and between experts and local SASPIC rheumatologists increased after review of imaging data. For pf-rheumatologists concordance with experts increased after review of imaging for 2 assessors and decreased for the other 2 assessors. For the latter, the primary reason for decrease in concordance with experts was false positive diagnosis of axSpA in 35% and 30% of the cases after review of the imaging. Conclusion: A structured case-based and sequential evaluation of clinical and imaging data suggests a gap in the training of recently graduated rheumatologists, with over-interpretation of imaging leading to false positive diagnosis of axSpA. Disclosure of Interests: Walter P. Maksymowych Grant/research support from: AbbVie, Novartis, Pfizer, and UCB, Consultant of: AbbVie, Boehringer Ingelheim, Celgene, Eli Lilly, Galapagos, Janssen, Novartis, Pfizer, and UCB, Employee of: Chief Medical Officer of CARE Arthritis Limited, Speakers bureau: AbbVie, Janssen, Novartis, Pfizer, and UCB, Liron Caplan: None declared, Atul Deodhar Grant/research support from: AbbVie, Eli Lilly, GSK, Novartis, Pfizer, UCB, Consultant of: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Speakers bureau: AbbVie, Amgen, Boehringer Ingelheim, Bristol Myer Squibb (BMS), Eli Lilly, GSK, Janssen, Novartis, Pfizer, UCB, Soha Dolatabadi: None declared, Mark Hwang: None declared, Adam Carlson: None declared, Kelly Steed: None declared, Amanda Carapellucci: None declared, Joel Paschke: None declared, Lianne S. Gensler Grant/research support from: Pfizer, Novartis, UCB, Consultant of: AbbVie, Eli Lilly, GSK, Novartis, UCB